Integral Absorbing Boundary Conditions Optimized for Modelling of Acoustic Radiation of Elongated Bodies. (22nd February 2022) - Salin, Mikhail B.; Smirnov, Sergey A.; Suvorov, Anatoliy S.; Usacheva, Irina A.; V'yushkina, Irina A.
Abstract : We propose a method of defining absorbing boundary conditions for use in finite element modeling of mechanoacoustic systems. The finite element model of an elastic body is expanded by a water domain, bounded by an axisymmetric surface, to which boundary conditions are applied. The boundary conditions are formed using the method of equivalent sources, so the integral relations for the pressure and its gradient are derived. The method retains its validity for the modeling of radiation in the low-frequency range, as it provides not only the absorption of outgoing waves but also the modeling of the added mass of vibrating elastic bodies.